Perfil epidemiológico de neonatos transportados para um hospital de referência materno-infantil - OLIVEIRA, Joanna Angélica Azevedo de (2019)
INTRODUCTION: In-hospital transport is conducive to the transfer of patients between hospital units, which may be of a public or private nature, which serve as the principle for the stabilization of critically ill patients. In the case of newborns, in the existence of complications and the need for a support that the place where the child is not, there arises the need for hospitalization or transference from one institution to the other, because the mortality risks in one preterm infants increase when labor occurs in a center with inadequate infrastructure. The knowledge of the profile of the newborns who needed inter-hospital transport for locomotion offers the possibility of surveying the possible factors that influence their survival, making them vulnerable and prone to hospital admission. OBJECTIVE: To investigate the clinical and epidemiological characteristics of newborns admitted to the Santa Casa de Misericórdia do Pará Foundation (FSCMPA) from interhospital transportation in the year 2016. METHODOLOGY: This is a retrospective descriptive, cross-sectional, documentary study, with a quantitative approach, which raised the epidemiological and clinical profile of the newborns who were transferred to FSCMPA through interhospital transport in the year 2016. It was carried out from the data / variables investigation in 100 charts, through a and were presented through tables and graphs that demonstrated the information that was classified and analyzed by means of statistical techniques. RESULTS AND DISCUSSION: We highlight the maternal epidemiological profile, in which the predominant age group was 25 to 34 years (34%); 41% underwent complete prenatal care and most had vaginal delivery (52%); 36% of the mothers had intercurrences during gestation, the most frequent being urinary tract infection with 23% of the cases and leucorrhea with 7%, among others. The variables of the epidemiological profile analyzed were: gestational age, anthropometric measurements, weight and Apgar, emphasizing that the latter presented values that differed from the normality standard; the epidemiological profile of the causes and the epidemiological profile were also collected and analyzed. time of neonatal hospitalization; it is worth mentioning that a critical point of the data analysis was the lack of information in the medical records, which are essential for the continuous care of the newborn. CONCLUSION: Knowing the epidemiological profile of the newborns who needed a transfer in search of more complex assistance becomes essential so that the team can identify the main factors that influenced the hospitalization of the newborn and the relevance of the registry of the newborn by the multiprofessional team, as a strategy of commitment, standardization, quality of care and allowance for decision-making regarding the size and impact of interhospital transport performed in the first days of life of this newborn.